A4.10 Forced exercise-induced osteoarthritis is attenuated in mice lacking the small leucine-rich proteoglycan decorin. (13th February 2015) - Gronau, T; Hansen, U; Seidler, DG; Iozzo, RV; Aszódi, A; Prein, C; Clausen-Schaumann, H; Krüger, K; Mooren, FC; Bertrand, J; Pap, T; Bruckner, P; et al.
Abstract : Background and objectives: Within cartilaginous extracellular matrix, the small leucine-rich proteoglycan decorin is located in the interterritorial regions among chondrocytes, where it is associated with well-banded collagen fibrils. In addition, decorin binds and inactivates TGF-β thereby regulating the bioactivity of this growth factor. In the present study, we have investigated biomechanical properties of decorin-deficient (Dcn -/- ) knee cartilage and the development of osteoarthritis (OA) induced by forced exercise. Materials and methods: OA was induced in 3 month-old Dcn -/- and wild-type (WT) mice via forced running on a treadmill and the severity of the disease was evaluated using a modified Mankin score. Knee articular cartilage of Dcn -/- and WT mice was analysed by histology/immunohistochemistry. Atomic force microscopy of unfixed, frozen tissue sections was used to measure the compressive stiffness of the articular cartilage. The amount of active TGF-β1 in the supernatant of cultured chondrocytes was determined by ELISA. Finally, we quantified via qPCR the expression of glycosaminoglycan- (GAG) modifying enzymes in chondrocytes following TGF-β1 treatment. Results: Both genotypes developed OA after six weeks of forced exercise. However, the phenotype was significantly less severe in Dcn -/- mice (Mankin score 4.5 in Dcn -/- vs. 6.5 in WT). Under unchallenged conditions, AFM analysis revealed an increased compressive stiffness of Dcn -/- cartilage. Stainings for highly sulfated GAGs via Alcian blue showed an increased intensity in Dcn -/- cartilage compared to WT littermates. In contrast, we found no alterations in staining for proteoglycan protein cores (e.g. aggrecan and biglycan) or collagens (II, VI, IX). Importantly, we detected enhanced levels of active TGF-β1 in Dcn -/- chondrocytes. In vitro stimulation of WT chondrocytes with TGF-β1 led to an upregulation of chondroitin-4-sulfotransferase (C4ST-1), the enzyme responsible for transfer of sulfate groups to position 4 of N -acetylgalactosamine of chondroitin containing GAGs. These findings were corroborated by increased staining intensity of Dcn -/- cartilage using an antibody toward chondroitin-4-sulfate stubs, but no changes using an antibody against chondroitin-6-sulfate. Conclusions: Here, we show that Dcn -/- cartilage exhibits a higher amount of active TGF-β1 and that stimulation of chondrocytes with TGF-β1 results in an upregulation of C4ST-1. The latter GAG-modifying enzyme leads to an enhanced expression of chondroitin-4-sulfate. This increase in negative charge might result in an augmented immobilisation of water, thereby providing a mechanistic explanation for the higher compressive stiffness of Dcn -/- cartilage, which results in less severe OA development after forced exercise.